The relationship between academic self-concept, attainment and personality in 16-19 year old students in a sixth form college - Summerfield, Eileen Margaret (1995)
The research examines a cohort of 364 16-17 year old students entering a sixth form college. The focus of the research is an examination of the relationship between academic self-concept, attainment and personality. Issues of gender and ethnicity were also examined. Data was obtained by the use of personality measures, students' self-estimates of success, examination results and information obtained from application forms, academic reports and Record of Achievement profiles. The students completed two personality measures on entry. The Student Self-Perception Scale was devised specifically for this research and was piloted on students from two sixth form colleges prior to use with the research sample. The Nowicki-Strickland Locus of Control Scale was also used as a validity measure. Basic statistics were obtained using a Pearson Product Moment correlation analysis and a frequency and cross-tabulation programme. A specific residual was generated using multiple linear regression analysis and used as a variable to indicate positive or negative attainment change.